A novel case study approach to the investigation of leg strength asymmetry and rugby league players' multidirectional speed - Helme, M.; Emmonds, S.; Low, C.; Till, K. (The Journal of Strength and Conditioning Research, 2024)
Leg strength and multidirectional speed qualities have repeatedly been linked with increased performance during Rugby League (RL) match play and associated with career attainment. However, very little of this evidence for strength has been gained through unilateral measurements with no study available that has examined the impact of strength asymmetry, in this population, on speed qualities in RL players. Therefore, this study examined the association between unilateral strength, and as a novel development, the subject with the most extreme asymmetry was identified for further analysis. Fifty RL players undertook the rear foot elevated split squat 5 repetition maximum, 20-m linear sprint, and modified 505 change of direction test. The mean leg strength for the group was 88.92 ± 12.59 kg; when divided by body mass, the mean relative strength (REL) was 1.03 ± 0.17 kg·kg-1, and the mean asymmetry was 3.21 ± 5.70%. The subject with the greatest asymmetry (subject A) had an imbalance of 33% and a mean leg strength of 75 kg (REL = 0.78 kg·kg-1) and a body mass 1 SD above the group mean. Analysis of the group's data and that of subject A did not indicate that leg strength asymmetry was either frequent or harmful, with respect to speed performance. However, relative leg strength was associated with both improved linear and multidirectional speed. Practitioners are recommended to prioritize the development of relative leg strength and disregard the aspiration for between leg performance symmetry.